2016
DOI: 10.1080/07357907.2016.1229332
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio (NLR) and Derived Neutrophil to Lymphocyte Ratio (d-NLR) Predict Non-Responders and Postoperative Complications in Patients Undergoing Radical Surgery After Neo-Adjuvant Radio-Chemotherapy for Rectal Adenocarcinoma

Abstract: In order to evaluate neutrophil-to-lymphocyte ratio (NLR) and derived neutrophil-to-lymphocyte ratio (d-NLR) in predicting response and complications in rectal cancer patients who underwent surgery after neo-adjuvant radio-chemotherapy, 87 patients were evaluated. Cutoffs before and after radio-chemotherapy were respectively 2.8 and 3.8 for NLR, and 1.4 and 2.3 for d-NLR. They were analyzed in relation to clinical and pathological outcomes. Patients with preoperative NLR and d-NLR higher than cutoffs had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 60 publications
5
46
2
Order By: Relevance
“…NLR has been reported to be correlated with patients' prognosis in different cancer studies. It has been reported that the pretreatment median NLR ranged from about 1.5 to3.3 (13,14,33).Forexample,ithasbeenreportedthata medianpreoperativeNLRof2.1wasofsignificantprognostic valuefordisease-specificmortalityinESCCpatientswhounderwentsurgery (34).Invariouscancerpatients,ithasbeen shownthatNLRcutoffsrangingfrom1.9to4.2wereofsignificantpredictivevaluefortreatmentresponses (12,18,35). Inthecurrentstudy,themedianpretreatmentNLRinESCC patientswasestimatedtobe2.3.Thisresultisconsistentwith previousstudies.Variousstudiesindifferentpatientpopulations haveidentified a relativelysmall variation in pretreatment NLR.…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been reported to be correlated with patients' prognosis in different cancer studies. It has been reported that the pretreatment median NLR ranged from about 1.5 to3.3 (13,14,33).Forexample,ithasbeenreportedthata medianpreoperativeNLRof2.1wasofsignificantprognostic valuefordisease-specificmortalityinESCCpatientswhounderwentsurgery (34).Invariouscancerpatients,ithasbeen shownthatNLRcutoffsrangingfrom1.9to4.2wereofsignificantpredictivevaluefortreatmentresponses (12,18,35). Inthecurrentstudy,themedianpretreatmentNLRinESCC patientswasestimatedtobe2.3.Thisresultisconsistentwith previousstudies.Variousstudiesindifferentpatientpopulations haveidentified a relativelysmall variation in pretreatment NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Caputo et al recently examined NLR and derived neutrophil-to-lymphocyte ratio (d-NLR) before and after nCRT in 87 rectal cancer patients. Higher NLR and d-NLR after nCRT was significantly associated with poor response to nCRT and postoperative complications [127]. Dong et al conducted a meta-analysis which included seven cohorts involving 959 patients to evaluate the prognostic value of NLR in patients with rectal cancer.…”
Section: Biomarkers In Bloodmentioning
confidence: 99%
“…17,18 Furthermore, CRP has been extensively investigated for its role in the prediction of post-operative complications and as an independent prognostic marker, [26][27][28] and it is widely used as a marker in monitoring for post-operative complications globally. 17,18 Furthermore, CRP has been extensively investigated for its role in the prediction of post-operative complications and as an independent prognostic marker, [26][27][28] and it is widely used as a marker in monitoring for post-operative complications globally.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a significant body of work studying the potential utilization of the NLR in predicting complications following gastrointestinal surgery, and it has been previously shown to be superior to WCC and CRP in this capacity. 17,18 Furthermore, CRP has been extensively investigated for its role in the prediction of post-operative complications and as an independent prognostic marker, [26][27][28] and it is widely used as a marker in monitoring for post-operative complications globally. However, we have demonstrated that the LMR may be more clinically useful in predicting such complications following liver resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation